ENVIRONMENTAL VARIABLES AND LEVELS OF MORALITY AMONG SECONDARY SCHOOL STUDENTS IN CALABAR EDUCATION ZONE OF CROSS RIVER STATE – NIGERIA AND COUNSELLING IMPLICATIONS. - Philip A. , Okpechi,; Arop, Lucy Obil ,; Edwin Okpa Bassey, (IJRDO- Journal of Educational Research, 2020)
The purpose of this study was to examine the influence of school environment variables on the level of morality among secondary school students in Calabar education zone of Cross River State, Nigeria. To guide the study, one hypothesis was formulated at 0.05 level of significance, using stratified random sampling. the instrument used for data collection was questionnaire titled Environmental Variables and Secondary School Students Morality Questionnaire (ESSMQ). The instrument had a reliability indices ranging from 0.705 to 0.871, using Chrombach alpha reliability estimate. The study adopted ex-post facto research design and the statistical tool for data analysis were simple linear regression and t-test. The result revealed that teacher-students’ relationship does not significantly influence the level of morality among secondary school students (F= .746, P= .388). The study therefore concluded that favourable school environment is a key to a positive, health, mental and moral development and recommended that school managers, school administrators should organize seminars, conferences and workshop that will motivate teachers to improve their level of class room management style to enhance and influence students’ morality.